Development of simple effective cloud of nodes and triangular mesh generators for meshless and element-based analyses – implementation in Matlab - Milewski, Sławomir (Computer Assisted Methods in Engineering and Science, 2017)
This paper is devoted to the development of the Matlab software dedicated to the generation of 2D arbitrarily irregular clouds of nodes and triangular meshes. They may be applied in numerical analyses of boundary value problems, based on both meshless and finite element discretization techniques, especially in the case of numerical homogenization in which the domain partitioning into disjoint subdomains may be required. Several Matlab functions are extended on the basis of the simple computational geometry-based ideas and concepts of engineering nature. A set of Matlab functions, attached to this paper, is discussed in detail, and examined on selected boundary value problems.